Insufficient evidence exists to use histopathologic subtype to guide treatment of idiopathic multicentric Castleman disease. Issue 12 (25th September 2020) - Fajgenbaum, David C.; Wu, David; Goodman, Aaron; Wong, Raymond; Chadburn, Amy; Nasta, Sunita; Srkalovic, Gordan; Mukherjee, Sudipto; Leitch, Heather; Jayanthan, Raj; Ferrero, Simone; Sato, Yasuharu; et al.
Abstract: Idiopathic multicentric Castleman disease (iMCD) is a rare immunologic disorder characterized by systemic inflammation, multicentric lymphadenopathy, and organ dysfunction. Enlarged lymph nodes demonstrate a spectrum of characteristic but variable histopathologic features historically categorized into hyaline vascular (HV) (or hypervascular [HyperV] more recently), plasmacytic, or "mixed." Though the etiology is unknown, a pro‐inflammatory cytokine storm, often involving interleukin‐6 (IL‐6), contributes to pathogenesis. Anti‐IL‐6 therapy with siltuximab is the only FDA‐ or EMA‐approved treatment based on efficacy and safety in multiple studies. Importantly, no patients considered to have HV histopathology achieved the primary endpoint in the Phase II study. NCCN currently recommends siltuximab first‐line for iMCD, except for patients considered to have HV histopathology. We investigated whether histopathologic subtype should guide siltuximab treatment decisions. Secondary analyses of clinical trial and real‐world data revealed similar clinical benefit across histopathologic subtypes. Notably, only 18 of 79 patients in the Phase II study were consistently classified into histopathologic subtype by three independent review panels, demonstrating limited reliability to guide treatment decisions. Real‐world data further demonstrate siltuximab's effectiveness in patients considered to have HV (or HyperV). Though histopathology is a critical component for diagnosis, there is insufficient evidence to guide treatment based solely on lymph node histopathologic subtype.